Synthesis and reactivity of the di(9-anthryl)methyl radical - Nishiuchi, Tomohiko; Takahashi, Kazuma; Makihara, Yuta; Kubo, Takashi (Beilstein Journal of Organic Chemistry, 2024)
The di(9-anthryl)methyl (DAntM) radical was synthesized and investigated to elucidate its optical, electrical properties, and reactivity. The generation of the DAntM radical was confirmed by its ESR spectrum, which showed two broad signals. The unpaired electron is primarily localized on the central sp2 carbon and slightly delocalized over the two anthryl moieties. Although the DAntM radical undergoes dimerization in solution, the radical still remains even at 190 K due to the bulky nature of the two anthryl groups. Interestingly, upon exposure to air, the purple color of the radical solution quickly fades to orange, resulting in decomposition to give 9-anthryl aldehyde and anthroxyl radical derivatives.
Keywords: anthracene; cation; dimerization; radical; reactivity